A Multifunctional Coating Strategy for Promotion of Immunomodulatory and Osteo/Angio‐Genic Activity. (17th November 2022) - Xiao, Shiqi; Wei, Jiawei; Jin, Shue; Xia, Xue; Yuan, Li; Zou, Qin; Zuo, Yi; Li, Jidong; Li, Yubao
Abstract: Building of multifunctional coatings in a more effective way is crucial for meeting the multilevel requirements of regenerative medicine. Herein, inspired by diatom and mussel, a specific but universal approach is proposed for building multifunctional coatings on slow‐degradable and fast‐degradable scaffolds or various substrates by using epigallocatechin gallate (EGCG) and polyethyleneimine (PEI) as bridges of silicon coupling. The results reveal that the polyphenol EGCG facilitates silica precipitation and coating topological morphology in synergy with PEI, and realizes antioxidant and immunomodulatory effects. The introduction of EGCG and the release of silicon ions present effective modulation of the immune microenvironment and remarkable promotion of angiogenesis and osteogenesis. The EGCG/silica coating strategy demonstrates a promising perspective for designing multifunctional coatings and optimizing tissue regeneration and reconstruction. Abstract : A universal method for preparing multifunctional silica coatings using bio‐inspired strategies. Epigallocatechin gallate in the coating layer not only assists silica deposition by bridging, but also plays an antioxidant and immune regulatory role. The combination of surface features and structural integrity maintenance of silica‐coated poly (e‐caprolactone) scaffold presents a robust bone regeneration effect.